Enhanced stability and photovoltaic performance of planar perovskite solar cells through anilinium thiobenzoate interfacial engineering - Thambidurai, Mariyappan (2022)
Organic-inorganic halide perovskite absorbers remain top contenders for current photovoltaic technologies owing to their ability to attain high efficiency at relatively low cost. However, commercialization of perovskite solar cells remains difficult due to their poor long-term stability. Such instability is commonly attributed to the ease in defect formation within the polycrystalline absorber film as well as at the surfaces between the layers, acting as recombination centers, reducing the overall performance of the device. Introduction of suitable interfacial layers has proven effective in defect passivation, allowing enhanced device stability and improving photovoltaic performance. In this study, a novel anilinium thiobenzoate (ATB) interlayer is deposited between the perovskite/hole transport layer (HTL) interface. Since ATB contains functional groups such as sulfur and ammonium, favourable coordination with under-coordinated lead ions on the perovskite film allows significant reduction in recombination losses and enhancement of open-circuit voltage from 1.05 to 1.11 V. Apart from the paramount efficiency of 19.33%, the 10 mg/mL ATB passivated device also shows exceptional long-term stability whereby 92% of initial efficiency is retained despite storage in ambient conditions for 150 days. Hence, results from this study highlights the importance of device passivation in attaining superior device performance and long-term stability.